Autism Spectrum Disorder - A Complex Genetic Disorder - Ivanov, Hristo Y; Stoyanova, Vili K; Popov, Nikolay T; Vachev, Tihomir I (Folia Medica, 2015)
Autism spectrum disorder is an entity that reflects a scientific consensus that several previously separated disorders are actually a single spectrum disorder with different levels of symptom severity in two core domains - deficits in social communication and interaction, and restricted repetitive behaviors. Autism spectrum disorder is diagnosed in all racial, ethnic and socioeconomic groups and because of its increased prevalence, reported worldwide through the last years, made it one of the most discussed child psychiatric disorders. In term of aetiology as several other complex diseases, Autism spectrum disorder is considered to have a strong genetic component.